Phyllanthus longipetiolatus (Phyllanthaceae), a new species from São Paulo State, Brazil - Torres, Alícia Marques; Silva, Marcos José Da (Phytotaxa, 2022)
During a taxonomic revision of Phyllanthus sect. Phyllanthus subsect. Phyllanthus, a new species was found and is being described and illustrated here. Phyllanthus longipetiolatus, known from the state of São Paulo (Brazil), belongs to the previously mentioned section and is morphologically similar to P. niruri. However, the new species differs from the latter by its leaves with long petioles (1.4–1.9 mm long), staminate inflorescences in cincinni, staminate and pistillate flowers with long pedicels (3.8–4 mm long and 6.7–8 mm long, respectively), staminate disk and smooth seeds. Its distribution, habitat, phenology, and informal conservation status are presented.